Analysis of Riau Intraregional Inequality Over the Past Decade (Period 2010-2023) - Manurung, Afriandi; Syapsan, Syapsan; Taryono, Taryono (Westscience Press, 2025)
This study aims to analyze economic inequality between districts/cities in Riau Province over the past decade. The focus of the study includes identifying intraregional disparity trends, determinants, impacts, and development equity policies evaluation. The methods used include Williamson Index Analysis, Theil Index, Regression Analysis, and Impulse Response Function (IRF). Williamson Index shows that inequality between Riau regions follows a convergence pattern with an inverted U-shaped curve tending, means inequality initially increases but then decreases over time. Bengkalis, Siak, Rohul, Inhil, and Meranti districts are the main contributors to inequality, Bengkalis and Siak contribute due to above-average, while Rohul, Inhil, and Meranti contribute due to low-average. Theil Index shows that from 2011-2014 inequality occurred between regions, but since 2015-2023 inequality dominant within a group of regions. Factors such as infrastructure access, topography, natural resource distribution, and government policies are found to be the main determinants of inequality. Regions with good infrastructure and low topography tend to be more developed, while high natural resource distribution exacerbates inequality in developed and average regions, reduces inequality in disadvantaged regions. Inequality has an impact on increasing poverty in developed and average regions, as well as decreasing health quality in disadvantaged regions. IRF analysis shows that the government's expansionary policy is quite effective in reducing inequality in Riau. The implications of the study provide recommendations to the government to prioritize equitable infrastructure development and effective expansionary policies to reduce inequality by considering topographic conditions and natural resource distribution in promoting equity throughout Riau.